Q.4 - Nguyễn, Cừ; Nguyễn, Anh Vũ (H., 2010)
Giới thiệu các tác phẩm thơ của nhiều tác giả: Tố Hữu, Bích Khê, Phan Khôi, Huyền Kiêu, Cẩm Lai, Yến Lan, Vũ Đình Liên, Lưu Kỳ Linh...
Keywords: Văn học Việt Nam -- Thế kỷ XX; Thơ ca Việt Nam -- Thế kỷ XX